Impact of Terrorism on Financial Markets of Turkey: An Empirical Study - Algan, Nese; Balcilar, Mehmet; Bal, Harun; Manga, Muge (Ege Univ, Fac Economics & Admin Sciences, 2017)
The purpose of the study is to investigate the impact of terrorism on the Turkish financial market. We test for causality from terrorism index to returns and volatilities of 16 sector level stock indices using daily data from Jan 4, 1988 to May 24, 2016 and a recently developed nonparametric causality-intest test of Balcilar et al. (2016). The results show that there is no causality from terrorist activities to stock market returns. However, we find significant causality at various quantiles from terrorist activates to volatility of tourism, food and basic materials sectors.
Keywords: Financial markets; Terrorism; Nonparametric causality-in-quantiles test; Turkey